1967
DOI: 10.1071/ph670577
|View full text |Cite
|
Sign up to set email alerts
|

Further Spectral Observations of Grenade Glow Clouds in the Lower Thermosphere

Abstract: SummaryThe spectral energy distribution is given for the glow clouds resulting from the explosion of aluminized grenades in the range of altitude from 100 to 200 km. At night, over much of the spectral range from 300 to 800 nm, the spectrum is a continuum very similar to that of a black body at 4000-5000 o K. At twilight, emissions resulting from resonant scattering of sunlight by AI, K, Ba, Na, and AIO are superimposed on, and dominate, the continuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…From these results it can be shown that the maximum radiant power could be produced by reaction (2) were it chemiluminescent. However, this would give Al line emissions at night and, since they are not observed, we prefer to use the chemiluminescent reaction (Rosenberg 1963) k4 AIO+O ---+ AI02+hv, (3) and this is consistent with the observations of Johnson and Low (1967), who showed that the night-time continuum is detectable in twilight clouds as a weak feature underlying the strong AIO band emissions.…”
Section: (B) Light Emissionsupporting
confidence: 69%
See 4 more Smart Citations
“…From these results it can be shown that the maximum radiant power could be produced by reaction (2) were it chemiluminescent. However, this would give Al line emissions at night and, since they are not observed, we prefer to use the chemiluminescent reaction (Rosenberg 1963) k4 AIO+O ---+ AI02+hv, (3) and this is consistent with the observations of Johnson and Low (1967), who showed that the night-time continuum is detectable in twilight clouds as a weak feature underlying the strong AIO band emissions.…”
Section: (B) Light Emissionsupporting
confidence: 69%
“…For clarity the curves have not been plotted at the correct relative positions on the ordinate scale and only the slopes of the curves are significant. Johnson and Low (1967) have given some curves showing the relative strengths of the various emissions. I Al 396 nm…”
Section: (B) Twilight Glow Cloudsmentioning
confidence: 99%
See 3 more Smart Citations